Bleogens: Cactus-Derived Anti-Candida Cysteine-Rich Peptides with Three Different Precursor Arrangements - Loo, Shining; Kam, Antony; Xiao, Tianshu; Tam, James P. (Frontiers in Plant Science, 2017)
Cysteine-rich peptides (CRPs) play important host-defense roles in plants. However, information concerning CRPs in the Cactaceae (cactus) family is limited, with only a single cactus-derived CRP described to date. Here, we report the identification of 15 novel CRPs with three different precursor architectures, bleogens pB1-15 from Pereskia bleo of the Cactaceae family. By combining proteomic and transcriptomic methods, we showed that the prototype, bleogen pB1, contained 36 amino acid residues, a six-cysteine motif typical of the six-cysteine-hevein-like peptide (6C-HLP) family, and a two-domain precursor consisting of an endoplasmic reticulum (ER) and a mature domain. In contrast, the precursors of the other 14 bleogens contained a three-domain architecture with a propeptide domain inserted between the ER and the mature bleogen domain. Four of these 14 bleogens display a third type of architecture with a tandemly repeating bleogen domain. A search of the Onekp database revealed that <1% plant species possess three different precursor architectures for the biosynthesis of 6C-HLPs, including Lophophora williamsii, Pereskia aculeate, Portulaca cryptopetala, Portulaca oleracea, Portulaca suffruticosa, and Talinum sp.. NMR analysis confirmed that bleogen pB1 has cystine-knot disulfide connectivity as well as a two-beta-sheet and a four-loop structural fold that is similar to other 6C-HLPs. Sequence analysis, structural studies, and in silico modeling revealed that bleogen pB1 has a cation-polar-cation motif, a signature heparin-binding motif that was confirmed by heparin affinity chromatography. Cell-based assays showed that bleogen pB1 is nontoxic to mammalian cells but functions as an anti-Candida peptide. Taken together, our findings provide insight into the occurrence, functions and precursor architectures of CRPs in the cactus family.